Organic carbon pools in a Luvisol under agroforestry and conventional farming systems in the semi-arid region of Ceará, Brazil - Mendonça, Eduardo Sá; Maia, Stoécio Malta Ferreira; Xavier, Francisco Alisson S.; Oliveira, Teógenes Senna; Araújo Filho, João A. (Agroforestry Systems, 2007)
Many environmental benefits have been attributed to agroforestry systems in various ecosystems around the world. However, there is a limited amount of information to evaluate this agricultural system in the semi-arid region, specifically in the region of Ceará, Brazil. The objective of this work was to evaluate five agricultural (four agroforestry and one conventional) systems in order to test the hypothesis that the agroforestry systems promote an increase in the soil organic carbon stocks and organic carbon pools, thus improving soil quality. The following treatments were tested: agrosilvopasture (AGP), silvopasture (SILV), traditional agroforestry (TRAG), intensive cropping (IC), and native forest (NF). The soil samples were collected at four depths: 0–6, 6–12, 12–20 and 20–40 cm. Total soil organic carbon stocks and the organic carbon pools (microbial biomass-C, mineralizable-C, oxidizable-C, free, occluded light fraction organic matter, and C in the humic substances) were analyzed. After 5 years of experimental cultivation, the soil under the SILV system presented the best results for the attributes studied, preserving, and in some cases, improving these attributes, when compared to the other conditions. The traditional agroforestry system (TRAG) reduced total organic carbon stocks and, consequently, C in some organic matter compartments, indicating that the fallow period was not sufficient to maintain soil quality. The AGP and IC systems presented significant losses in some of the soil organic matter (SOM) pools, suggesting that the soil environment had been degraded. The most labile SOM components were considered sensitive indicators of change in the soil quality. The silvopasture system can, therefore, be recommended as an alternative soil management strategy for food production and for the maintenance of soil quality and agricultural sustainability in the semiarid region of Ceará state.
Keywords: Semi-arid; Agroforestry; Organic carbon pools; Soil quality